(untitled) (MAUSAM, 2007)
In this study, ET data available on Soybean crop for Bhopal during 1991-95 have been utilized. With regard to water need of the crop, the life span of soybean has been divided into five important growth stages viz., seedling up to 2 weeks after sowing (WAS), vegetative (3-8 WAS), flowering (9-10 WAS), pod development (11-13 WAS), and maturity (14-15 WAS). In this paper, consumptive use of water (ET), Water Use Efficiency (WUE), Heat Units (HU), Heat Use Efficiency (HUE) and crop coefficient (Kc) for different growth stages of the crop have been computed and discussed. The study revealed that on an average, Soybean crop consumed about 450 mm of water. The average WUE was found to be 3.23 kg /ha/mm. It was also observed that WUE does not depend only on the total amount of water consumed by the crop but also indicates the importance of its distribution during various growth stages. On an average, the crop consumed nearly 7%, 36%, 24%, 25% and 8% of water during seedling, vegetative, flowering, pod development and maturity stage respectively. The crop consumed maximum amount of water during vegetative stage. However, the average weekly ET rate was found to be highest during flowering stage (nearly 52 mm). Average heat unit requirement of soybean was found to be 1694 degree-days. Maximum heat units were required during vegetative stage (638 degree days) followed by pod development stage (358 degree days). The average HUE was found to be 0.86 kg/ha/degree days. Crop coefficient (Kc) values varied in the range 0.30 – 0.45, 0.55 – 0.90, 1.00 – 1.15, 0.85 – 0.70 and 0.55 – 0.40 during seedling, vegetative, flowering, pod development and maturity stage respectively. The crop coefficient values attained the peak during the flowering stage.